Associations of magnesium depletion score with the incidence and mortality of osteoarthritis: a nationwide study - Ma, Ruicong; Zhang, Cheng; Liu, Jiaqing; Ren, Jinyi; Huang, Huina; Wang, Guan; Ding, Yanchun; Li, Xia (Frontiers in Immunology, 2025)
BackgroundMagnesium is an essential immune nutrient for the body, and recent studies have found that it plays an important role in osteoarthritis (OA). Magnesium depletion score(MDS) is a new method for evaluating the magnesium status of the body. Our objective is to explore the association between MDS and the incidence of OA, as well as the relationship between MDS and mortality in patients with OA.MethodsEligible participants were obtained from NHANES from 2005 to 2018. Logistic regression models were employed to evaluate the link between MDS and the incidence of OA. Cox regression models were employed to evaluate the link between MDS and mortality among OA patients. In addition, restricted cubic spline was utilized to explore the correlation between MDS and the incidence of OA, as well as the relationship between MDS and mortality in patients with OA. Subgroup analysis were adopted in order to ensure the credibility of the results in different subgroups, including age, gender, race, education level, BMI, smoking, diabetes and hypertension.Results19,394 individuals qualified for analysis, including 3,256 OA patients. After excluding missing follow-up data, 630 all-cause deaths and 172 cardiovascular deaths (CVDs) were observed in 3,250 OA patients. The individuals with OA had higher levels of MDS. In the logistic regression model, MDS was positively related to OA (MDS≥3 vs. MDS=0, OR =1.83 (1.46-2.30, P<0.001)). Besides, a positive association was observed between MDS and all-cause mortality [MDS≥3 vs. MDS=0, HR =2.56 (1.49-4.41, P<0.001)] and CVDs [MDS≥3 vs. MDS=0, HR =3.00 (1.13-7.98, P=0.01)] in cox regression models. In addition, a 1-unit rise in MDS was significantly linked to an increased risk of mortality. Restricted cubic spline indicated a positive relationship between MDS and incidence and mortality of OA. Subgroup analysis demonstrated that the results are stable in different subgroups.ConclusionsMDS is positively correlated with the incidence and mortality of OA. Optimizing the nutritional status of magnesium may bring benefits to OA patients.